Application of Islamic Consumption Theory to Students of Economics Faculty, Universitas Bangka Belitung - Rahmani, Zikri; Eka, Eka Fitriyanti (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2024)
The current phenomenon shows that the lifestyle of students in the economics study program has entered the modernization era, in which society is increasingly consumerist. People will continue to consume, but the habitual consumption pattern is no longer just for fulfilling basic needs and functional needs, but has become a lifestyle and is excessive. The aim of this activity is to increase the knowledge and understanding of students in the Economics Study Program at Bangka Belitung University to apply Islamic consumption concepts and values in daily economic activities. This Community Service activity consists of two stages, namely the preparation and implementation stages of the activity. The preparation stages consist of coordination meetings, preparation of questionnaires and survey objects. The stages of implementing the activity consist of a lecture, brainstorming and ending with question and answer. The results of community service activities are providing education and understanding about the application of consumption theory in sharia economics, such as; Consumption for good (Maslahah), prohibition on doing Isrof, prohibition on tabzir, orders and recommendations for sharing and so on. The conclusion of this service activity increases the knowledge of Bangka Belitung University Economics Study Program students regarding the application of consumption theory in sharia economics to their daily consumption activities.